Iron deficiency in therapeutic practice. The specifics of iron deficiency and iron deficiency anemia prevention - G. N. Gorokhovskaya (Медицинский совет, 2014)
The article tells about the etiology and pathogenesis of iron deficiency, clinical manifestations and principles of treatment of iron deficiency anemia. The choice of drug therapy is highlighted. The advantages of non-ionic iron preparations (Maltofer) for patients with iron deficiency anemia are provided.